Java to Python in 100 easy steps : the fastest way to learn Python for experienced Java programmers - Karanam, Ranga (Packt Publishing, 2018)
"This course will help you learn Python, one of the most popular programming languages. Python offers both object oriented and structural programming features. We take a hands-on approach using a combination of Python Shell and PyCharm as an IDE to illustrate more than 100 Python coding exercises, puzzles, and code examples. We convert a number of Java examples to Python. You will learn about implementing Object Oriented Programming concepts in Python, inheritance, abstract classes, and constructors; you will also get a better understanding of a wide variety of Python data structures: lists, sets, dictionaries, and tuples."--Resource description page